FINDRISC, utility in the screening of diabetes, personalization and associations: FINDRISC, utilidad en el screening de diabetes, personalización y asociaciones - Campos, Nestor (2018)
ABSTRACT Introduction: We are currently experiencing the diabetes pandemic, in 2017 the "International Diabetes Federation" reported that 425 million adults have diabetes. Within the prevention and screening we have FINDRISC (Finnish Diabetes Risk Score), a test that is being widely used, so we must review the available evidence, if it has sufficient predictive capacity to be recommended and used, if there is personalization according to sociodemographic patterns, and if it has relationships. Methods: In this systematic review article, the information was compiled from PubMed, Elsevier library, ScienceDirect, BMJ Journals and “Revista de la facultad de Medicina Humana de la URP. Results: Of 30 articles found, 23 were selected: 12 were analytical, 7 descriptive, 2 cases and control, 2 clinical trials. Conclusion: The average AUC is 77.81%, so it has sufficient positive predictive capacity. 91% suggest its use, 35% of studies have personalized it and can be linked to metabolic syndrome, subclinical vascular complications and quality of life. Key words: FINDRISC; Metabolic syndrome; Prediabetic state; Obesity; Health Survey; Diabetes Mellitus, Type 2, Detection, Risk; Public health. (source: MeSH NLM) DOI:  10.25176/RFMH.v18.n3.1594